Towards efficient synthesis of sugar alcohols from mono- and poly-saccharides: role of metals, supports & promoters - Tathod, Anup P.; Dhepe, Paresh Laxmikant (Green Chemistry, 2014)
{Biomass derived sugar alcohols (xylitol, arabitol) find numerous uses in the food, oral hygiene and pharmaceutical industries. Their direct synthesis from poly-saccharides, however, still remains an immense challenge. In this study, we demonstrate in detail the effects of metals, supports and promoters in enhancing the yields of sugar alcohols from mono- and poly-saccharides. We undertook synthesis of bimetallic catalysts, M-M'/S (M

Efficient method for the conversion of agricultural waste into sugar alcohols over supported bimetallic catalysts - Tathod, Anup P.; Dhepe, Paresh Laxmikant (Bioresource Technology, 2015)
Promoter effect of Sn in the PtSn/gamma-Al2O3 (AL) and PtSn/C bimetallic catalysts is studied for the conversion of variety of substrates such as, C5 sugars (xylose, arabinose), C6 sugars (glucose, fructose, galactose), hemicelluloses (xylan, arabinogalactan), inulin and agricultural wastes (bagasse, rice husk, wheat straw) into sugar alcohols (sorbitol, mannitol, xylitol, arabitol, galactitol). In all the reactions, PtSn/AL showed enhanced yields of sugar alcohols by 1.5-3 times than Pt/AL. Compared to C, AL supported bimetallic catalysts showed prominent enhancement in the yields of sugar alcohols. Bimetallic catalysts characterized by X-ray diffraction study revealed the stability of catalyst and absence of alloy formation thereby indicating that Pt and Sn are present as individual particles in PtSn/AL. The TEM analysis also confirmed stability of the catalysts and XPS study disclosed formation of electron deficient Sn species which helps in polarizing carbonyl bond to achieve enhanced hydrogenation activity. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Agricultural waste; Bimetallic catalyst; Hydrogenation; Monosaccharides; Polysaccharides

Elucidating the effect of solid base on the hydrogenation of C5 and C6 sugars over Pt–Sn bimetallic catalyst at room temperature - Tathod, Anup P.; Dhepe, Paresh L. (Carbohydrate Research, 2021)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Conversion of sugars into <a class="topic-link" href="https://www.sciencedirect.com/topics/biochemistry-genetics-and-molecular-biology/sugar-alcohols" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px;" title="Learn more about sugar alcohols from ScienceDirect's AI-generated Topic Pages">sugar alcohols at room temperature with exceedingly high yields are achieved over Pt–Sn/γ-Al<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">3<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> catalyst in the presence of calcined <a class="topic-link" href="https://www.sciencedirect.com/topics/biochemistry-genetics-and-molecular-biology/hydrotalcite" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px;" title="Learn more about hydrotalcite from ScienceDirect's AI-generated Topic Pages">hydrotalcite. pH of the reaction mixture significantly affects the conversion and selectivity for sugar alcohols. Selection of a suitable base is the key to achieve optimum yields. Various solid bases in combination with Pt–Sn/γ-Al<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">3<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> catalysts were evaluated for hydrogenation of sugars. Amongst all combinations, the mixture (1:1 <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">wt/wt<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">) of Pt–Sn/γ-Al<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">3<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> and calcined hydrotalcite showed the best results. Hydrotalcite helps to make the pH of reaction mixture alkaline at which sugar molecules undergo ring opening. The sugar molecule in open chain form has <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/carbonyl-group" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px;" title="Learn more about carbonyl group from ScienceDirect's AI-generated Topic Pages">carbonyl group which can be polarized by Sn in Pt–Sn/γ-Al<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">3<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> and Pt facilitates the hydrogenation. In the current work, effect of both; solid base and Sn as a promoter has been studied to improve the yields of sugar alcohols from various C5 and C6 sugars at very mild reaction conditions.
Keywords: Bimetallic catalyst; Hydrogenation; Hydrotalcites; Sugar; Sugar alcohols